Respuesta :
4x + 3y = 16
7x + 6y = 31
Note what happens if we mult. the first eqn. by -2:
-8x - 6y = -32
Combining this with the 2nd equation eliminates the variable y:
-8x - 6y = -32
7x + 6y = 31
--------------------
-x = -1, or x = 1. Sub 1 for x in either of the 2 given eqns to find y:
For example: 4(1) + 3y = 16, so 36 = 12, and y = 3. Sol'n is (1,3).
7x + 6y = 31
Note what happens if we mult. the first eqn. by -2:
-8x - 6y = -32
Combining this with the 2nd equation eliminates the variable y:
-8x - 6y = -32
7x + 6y = 31
--------------------
-x = -1, or x = 1. Sub 1 for x in either of the 2 given eqns to find y:
For example: 4(1) + 3y = 16, so 36 = 12, and y = 3. Sol'n is (1,3).
Answer:
1,4
Step-by-step explanation:
The correct answer is (1,4)